Proceedings 1999 International Conference on Image Processing (Cat. 99CH36348)
DOI: 10.1109/icip.1999.817191
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the color information in face recognition

Abstract: A common feature found in practically all technical approaches proposed for face recognition is the use of only the luminance information associated to the face image. One may wonder ifthis is due to the low importance of the color information in face recognition or due to other less technical reasons such as the no availability of color image database. Motivated by this reasoning, we have performed a variety of tests using a global eigen approach developed previously [I], which has been modfied to cope with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
1

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 5 publications
1
82
1
Order By: Relevance
“…The common approach in most of the face recognition systems is to convert the color images to monochromatic form using simple transformations. There was also another approach where the RGB space has been compared with the YUV and HSV color models by L. Torres [8] for PCA based face recognition. Several studies have been made to evaluate color spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The common approach in most of the face recognition systems is to convert the color images to monochromatic form using simple transformations. There was also another approach where the RGB space has been compared with the YUV and HSV color models by L. Torres [8] for PCA based face recognition. Several studies have been made to evaluate color spaces.…”
Section: Introductionmentioning
confidence: 99%
“…For face recognition, the eigenface analysis in the RGB color space domain is known not to be effective, because R, G, and B components are largely correlated with each other. Some literatures also pointed that the RGB domain is inadequate for face recognition (Torres et al, 1999). Instead of RGB color space, other color spaces that are less correlated between their components should be investigated for face recognition.…”
Section: Color Spaces For Face Recognitionmentioning
confidence: 99%
“…1(a). The final decision is made with the distances from three independent www.intechopen.com eigenface modules (Torres et al, 1999). Fig.…”
Section: Independent Color Face Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, face recognition systems have operated in the two-dimensional (21)) space. Most systems use digitised gray-scale photographs of faces (intensity images), though some research involving colour images is also found in literature (Torres et al 1999). Intensity images measure the amount of light reflecting from a surface and hitting a photosensitive device (camera).…”
Section: Automated Face Recognitionmentioning
confidence: 99%